2020
DOI: 10.3390/su12124817
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Sustainable Engineers: A Project-Based Learning Experience in Logistics with Refugee Camps

Abstract: This article describes an intrinsic case study of project-based learning (PBL) experience involving an NGO as an external client to promote sustainability competencies. Two research questions are posed: (1) How did this experiential PBL approach impact students learning to develop sustainability competencies by incorporating a responsible engineering perspective? (2) How did college students become engaged with social and sustainable PBL projects when external clients of developing economies were involved? The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…This approach type could enrich knowledge (Foster and Stagl, 2018; Savelyeva and Douglas, 2017), raise awareness (Kalsoom and Khanam, 2017), develop a sense of agency (Merritt et al , 2018), acquire competency (e.g. autonomous learning, global mindset, ability to solve problems and decision-making) (Terrón-López et al , 2020) and influence PEB of students (Pearson et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach type could enrich knowledge (Foster and Stagl, 2018; Savelyeva and Douglas, 2017), raise awareness (Kalsoom and Khanam, 2017), develop a sense of agency (Merritt et al , 2018), acquire competency (e.g. autonomous learning, global mindset, ability to solve problems and decision-making) (Terrón-López et al , 2020) and influence PEB of students (Pearson et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies focused on more specific topics such as food (Albareda-Tiana et al, 2018), textile and apparel industry (Abner et al, 2019) and sustainable consumption (Collins et al, 2018), thus, providing students with new viewpoints based on the triple bottom line approach of sustainability. Additionally, some papers focused on the development of innovative and transdisciplinary teaching methodologies based on active and experiential learning (Albareda-Tiana et al, 2018;Foster and Stagl, 2018;Cazorla-Montero et al, 2019;Terr on-L opez et al, 2020) or based on the use of new tools (e.g. ecological footprint calculator) to address daily personal problems (Collins et al, 2018).…”
Section: Educationmentioning
confidence: 99%
“…Sustainable logistics ensure sustainable consumption of resources leading to effective resource management (SDG 12), reduced air pollution (SDG 3) and safe working conditions (SDG 8). From the literature, it is observed that project‐based learning helps students to understand the SDGs for their effective implementation in logistics as experiential learning enables the student to develop their sustainable competencies for effective implementation (Terrón‐López et al, 2020). Studies also reveal that institutional theory and information technologies act as enablers for sustainable performance of logistic operations (Zawawi et al, 2018).…”
Section: Content Analysismentioning
confidence: 99%
“…In these works, there is empirical evidence that the use of these active methodologies not only improves the competences of students, but also serves to make them aware of their future requirements, increase their motivation and involvement in the subjects they take, and also expand skills such as creativity. On the other hand, recent works by [59][60][61][62] on blended learning, problem-based learning, and project-based learning can be seen, as the topics addressed focus on the favorable opinions of students and teachers on these types of active methodologies, as well as on the acquisition of various kinds of skills. Through this overview, it can be observed that, over recent years, innovative actions have been aimed at digital updating and technological exploitation in the ambit of higher education through a series of active methodologies centered on students.…”
Section: Findings Of the Researchmentioning
confidence: 99%